ESSENCE OF BASIC CONCEPTS OF PUBLIC ADMINISTRATION IN SAFETY MANAGEMENT OF SOLID WASTES - Sоbоl O.М.; Olenychenko Yu.A. (Pressing Problems of Public Administration, 2015)
The essence of basic conceptual categories of public administration in the field of safetymanagement of solid wastes is defined. The mainstream for further research in this area isoutlined.